Effect of tactile experiences on facial emotion perception - Lee, Xue Er (Nanyang Technological University, 2022)
In perceiving facial expressions, we usually rely on visual information of the faces. However, humans receive and process information from their external world by combining information from multiple sensory modalities. While previous studies showed a significant cross-modal effect of vision on the perception of tactile experiences, the effect of touch on vision was inconsistent and poorly understood. This paper aimed to investigate how tactile experiences will affect visual perception, specifically the perception of facial expressions. Sixty Nanyang Technological University students were recruited for the main study and randomly assigned to either one of the tactile conditions: soft and smooth (SS), hard and rough (HR), or control conditions. Participants rated the emotional intensity of the facial expressions with (SS, HR) or without (control) a tactile stimulus being held with their left hand. Six Implicit Association Tests (IATs) were used to examine participants’ implicit attitudes toward softness and texture. The results indicated a significant cross-modal effect of touch on vision, in which the anger ratings in the HR condition were consistently higher than that in the control condition. IAT results showed participants relatively tended to associate softness and smoothness with happiness and positive valence while hardness and roughness were more associated with fear, anger, and negative valence. This present study suggests that human recognition of facial expressions can be influenced by tactile perception at the same time. Therefore, it indicated multisensory integration in emotion perception from tactile to vision.